Assessment of Measurement System Capability: A Case Study on Complex Geometry Parts - Durakovic, Benjamin; Obarčanin, Haris (International Journal of Industrial Engineering: Theory, Applications and Practice, 2024)
This paper discusses the most fundamental problem related to the variation of the complex geometry part manufacturing process caused by the variation of the measuring system, and it outlines potential solutions. Optical measuring instruments are frequently used for measurements of complex geometry, but the complex features hinder uniform part illumination, which makes accurate measurement more challenging. The aim of this research is to identify measurement variation sources that are significant to the manufacturing process variation. For the comparison of the capabilities of the measurement system, the two most frequent measuring devices used in the process are analyzed (digital micrometer and 3D coordinate measuring machine (CMM)). The data analysis method in this research is based on measurement system capability indices (Cg and Cgk). It was found that the Cg and Cgk indices are greater than the threshold value of 1.33, whereas the repeatability R and accuracy and repeatability A&R indices are less than the threshold of 15%. However, results showed that the absolute error is significantly higher with micrometer measurements, identifying the micrometer as a major source of the variation, which, in the end, affects the manufacturing process and misleads decision-makers to make wrong conclusions.